THE EFFECTIVENESS OF LEARNING USING COMIC MEDIA IN REDUCING BULLYING IN CLASS V ELEMENTARY SCHOOL - Elza Eka Lestari; Firman (Jurnal Penelitian Pendidikan IPA, 2025)
Weak character education causes deviant behavior such as bullying behavior that often occurs in the school environment. Bullying behavior is one example of deviant and dangerous behavior characterized by the intention to hurt, power imbalance, mocking parents' names, making fun of physical conditions. Students do not fully understand the dangers of bullying behavior for mental health so that learning is needed using media in the form of comics. The objectives of this study are: to analyze bullying behavior experienced by students in the experimental group before and after implementing learning with comic media; to analyze the differences in bullying behavior experienced by students in the control group before and after implementing learning without comic media; to analyze the effectiveness of implementing learning using comic media between the experimental group and the control group without using comic media. The study used a quasi-experimental pretest-posttest control group design method. The population was 45 fifth grade students of SD Negeri Gugus 1 Kec. Siulak Mukai. The sampling technique was cluster random sampling totaling 30 students. The research instrument used a Likert scale. The data were analyzed using parametric statistics, namely Paired T-Test (T-Test) and Independent Sample T-Test. The results of the study showed: there was a significant difference before and after learning using comic media was given to the experimental group; There was no difference before and after learning without using comic media was given to the control group; there was a significant difference in the effectiveness of learning using comic media in the experimental group with the control group learning without using comic media. Therefore, learning using comic media is effective in reducing student bullying behavior.